Accessibility of disabled toilet for wheelchair user in public buildings in Kuala Lumpur / Najiebah Majdi - Najiebah, Majdi (2021)
According to Department of Statistics Malaysia, the highest number of People with Disabilities (PWD) registered have physical disabilities where this group of people face difficulties in moving and executing task. As the population of PWDs in Malaysia is increasing, the demand for the right to access public buildings such as government institutions, transportations, tourist attractions and healthcare also has been rising especially in Kuala Lumpur. In this research, disabled toilet has been selected as the main facility to be assessed. Therefore, the two objectives for this study are to assess the accessibility of disabled toilet in public buildings in Kuala Lumpur and to evaluate the compliance or applicability of Malaysian Standard in the design of the disabled toilet. In order to measure the accessibility of disabled toilet, questionnaire survey is conducted where respondent’s view and opinion on current condition of disabled toilet are collected. Next, two public building of four sectors which are healthcare, tourism, business or retails and transportation been chosen and access audit are been done by comparing the measurement with guidelines provided in Malaysian Standard (MS 1184:2014): Universal Design And Accessibility In The Built Environment. Based on the result obtained, it can be observed that Transportation sector received the lowest score for both in term of accessibility and applicability of Malaysian Standard while Healthcare and Business or Retails has the highest score which indicated that these two sectors had done a great job providing a barrier free facility. Items that need improvements are the height of toilet paper and installing an emergency alarm inside every disabled toilet.